The Covenant Connection Reexamined: The Nexus between Religions and Federalism in Asia. (August 2018) - He, Baogang; Allison-Reumann, Laura; Breen, Michael
The covenant connection thesis forms an important basis from which to understand the religious source of federalism. Yet with its Judeo-Christian roots, to what extent does it apply to Asian countries that have different religious traditions? In this article, we explore whether the covenant connection thesis is relevant to Asian federalism in the context of Muslim-, Hindu-, and Buddhist-majority countries. We find that while the presence or absence of a covenantal tradition within a religion can partially explain acceptance of, or resistance to, federalism, there are other religious features that also play a role. These include the extent to which traditional religious organizations are internally centralized, the extent to which religion and state governance are intertwined or separate from each other, and the extent to which a religion that constitutes the core national identity is threatened by other religions that are or may be empowered by federal arrangements.